Understanding cross-cultural psychology : eastern and western perspectives - Laungani, Pittu D. (Sage Pub, 2007)
This textbook introduces students to global perspectives on cross-cultural psychology, encompassing both Eastern and Western cultures. It includes a variety of features designed to enhance student learning, such as vignettes, case studies, and other engaging text elements. Additionally, it explores international research in the field of cross-cultural psychology.
Includes bibliographical references and index.
Keywords: Psychology; Ethnopsychology; Cultural psychology